2021
DOI: 10.3390/catal12010013
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ce and W Promoters on the Performance of Alumina-Supported Nickel Catalysts in CO2 Methanation Reaction

Abstract: The influence of Ce and W promoters on the performance of alumina-supported nickel catalysts in the CO2 methanation reaction was investigated. The catalysts were obtained by the co-impregnation method. Nitrogen low-temperature adsorption, temperature-programmed reduction, hydrogen desorption, transmission electron microscopy, X-ray diffraction, and photoelectron spectroscopy studies were used for catalyst characterization. An introduction of Ce and W promoters (1–5 wt %) led to the decrease in mean Ni crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It has been realized that a small change in the catalyst synthesis procedure might poses a substantial effect on the outcome of such a catalyst concerning catalyst structures, consequently having noteworthy differences in catalytic activity and selectivity, [161]. To further emphasize the importance of the catalyst preparation method, more latest experiments by Ai et al utilizing tungsten-doped Ni/Al2O3 catalysts, has shown that in CO methanation the addition of tungsten enhances reducibility and accordingly improves the number of active sites as well process performance but only when the appropriate preparation procedure is used [162].…”
Section: Effects Of Preparation On Activity and Product Selectivitymentioning
confidence: 99%
“…It has been realized that a small change in the catalyst synthesis procedure might poses a substantial effect on the outcome of such a catalyst concerning catalyst structures, consequently having noteworthy differences in catalytic activity and selectivity, [161]. To further emphasize the importance of the catalyst preparation method, more latest experiments by Ai et al utilizing tungsten-doped Ni/Al2O3 catalysts, has shown that in CO methanation the addition of tungsten enhances reducibility and accordingly improves the number of active sites as well process performance but only when the appropriate preparation procedure is used [162].…”
Section: Effects Of Preparation On Activity and Product Selectivitymentioning
confidence: 99%